Afterslip Enhanced Aftershock Activity During the 2017 Earthquake Sequence Near Sulphur Peak, Idaho. Issue 11 (5th June 2018) - Koper, Keith D.; Pankow, Kristine L.; Pechmann, James C.; Hale, J. Mark; Burlacu, Relu; Yeck, William L.; Benz, Harley M.; Herrmann, Robert B.; Trugman, Daniel T.; Shearer, Peter M.
Abstract: An energetic earthquake sequence occurred during September to October 2017 near Sulphur Peak, Idaho. The normal‐faulting M w 5.3 mainshock of 2 September 2017 was widely felt in Idaho, Utah, and Wyoming. Over 1, 000 aftershocks were located within the first 2 months, 29 of which had magnitudes ≥4.0 M L . High‐accuracy locations derived with data from a temporary seismic array show that the sequence occurred in the upper (<10 km) crust of the Aspen Range, east of the northern section of the range‐bounding, west‐dipping East Bear Lake Fault. Moment tensors for 77 of the largest events show normal and strike‐slip faulting with a summed aftershock moment that is 1.8–2.4 times larger than the mainshock moment. We propose that the unusually high productivity of the 2017 Sulphur Peak sequence can be explained by aseismic afterslip, which triggered a secondary swarm south of the coseismic rupture zone beginning 1 day after the mainshock. Plain Language Summary: During the fall of 2017, an energetic sequence of earthquakes was recorded in southeastern Idaho. The mainshock had a moment magnitude of M w 5.3, yet thousands of aftershocks were detected. We found that the unusually high productivity of this earthquake sequence can be explained by extra sliding that occurred just after the mainshock. This extra sliding happened too slowly to generate seismic waves, but it was large enough to alter the stress in the crust such that the extra aftershocks were created. Our finding suggests that in this region of Idaho, some of the strain that is built up by tectonic forces is released in slow‐slip or creep events. This discovery will ultimately lead to more accurate forecasts of seismic hazard in the region. Key Points: The 2017 Sulphur Peak earthquake sequence was very energetic, with a summed aftershock moment 1.8–2.4 times that of the M w 5.3 mainshock Magnitude‐time histories are consistent with a standard mainshock‐aftershock sequence augmented by an afterslip‐driven swarm The 2017 sequence is co‐located with swarm‐like sequences from 1960 and 1982, implying that SE Idaho may be prone to repeating creep events